Destination preference and self-image congruity. - Goh, Hwai Kar. (2008)
This study examines self-image congruity and its relationship with pre-visit destination interest and travel proclivity in a family vacation situation. This research also explores the concept of family image, a psychological characteristic of the family and studied how family image is related to the relative influence structure in family vacation decision-making.